Use of ICT in English Language Teaching Classroom - Bhandari, Bhim Lal; Bhandari, Sabina (Vox Batauli, 2024)
Information Communication Technology (ICT) in teaching and learning is indispensable for improving teachers' professional skills in English language teaching (ELT). This paper examines secondary English language teachers' experiences in using ICT in teaching English in Nepal. The extensive semi-structured interview as a key information-gathering strategy under the phenomenological research method was employed to explore the participants’ experiences in applying ICT skills in teaching English. Four English language teachers who had been using ICT in teaching for at least two years were selected purposively from two public secondary schools in Rupandehi, Nepal. The findings revealed that the use of ICT engages students' cognitive processes and their autonomy in class. It also creates an engaging and dynamic atmosphere for learning and facilitates better access to learning materials. The study can contribute to improving teaching and learning efficacy using ICT skills for effective teaching in public schools in Nepal.